C-terninal-truncated and full length hemeoxygenase-1 exert opposite behavior of head and neck cancer cells - Mascaró, Marilina (2019)
We previously reported that heme oxygenase-1 (HO-1) protein is up-regulated in human HNSCC samples and that it is localized in the cytoplasmic and nuclear compartments. We also reported that high expression of HO-1 mRNA is associated with worst survival and that pharmacological activation of HO-1 by hemin increases viability of HN13 cells. However, how full length (FL-HO1) and C-terminal truncated (t HO1) HO-1 affects HNSCC remains elusive. In this study, we aim to elucidate if such forms of HO-1 impacts on head and neck cancer cells behavior. We established the FL-HO1 and t-HO1 overexpressing HN13 cells. We evaluated cell viability by crystal violet method, cell cycle progression by propidium iodide staining and flow cytometry, and cell migration by wound healing assay. In addition to our previous results using hemin, we found that 80 µM hemin increased cell number in S- (p<0.001) and G2/M (p<0.001) phases and diminished cell number in Go/G1 phase (p<0.001) at 72h. We also found that hemin delayed cell migration (p<0.01) respect to control. On the contrary, at same conditions, hemin failed to increase cell viability (p>0.05) neither alters cell cycle progression (p>0.05) in the normal keratinocyte cell line, HaCaT. By a genetic approach, we found that FL-HO1 HN13 cells have a higher growth rate (p<0.001) than its control and cell cycle progression is as similar as (p<0,001 vs control) it was observed with hemin treatment. However, FL-HO1 failed to alter migratory capacity (p>0.05). We also found that t-HO1 expression impaired HN13 cell viability (p<0.01 vs. FL-HO1 HN13) and induces a Go/G1 arrest (p<0.01) and a diminished cell number in SubGo (p<0.01) and S- (p<0.05) phases. Also, we found that t-HO1 expression delayed cell migration (p<0.001) respect to FL-HO1 HN13. In conclusion, our results show that head and neck cancer cells survival, cell cycle progression and migration capacity depends on predominant HO-1 form.